Enhancing AODV protocol for black hole attack detection and mitigation in VANETs: a lightweight dual-confirmation approach - Ahmed Abderraouf; Ramdane Taglout; Sofiane Boukli-Hacene (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
Vehicular ad hoc networks (VANETs) represent a specialized category of Mobile ad hoc networks that are specifically designed to enable communication among autonomous (self-driving or partially self-driving) vehicles. These vehicles are equipped with onboard computers, network interfaces, and sophisticated sensors for data capture and processing. Within a VANET, vehicles have the ability to communicate with each other as well as with surrounding infrastructure, thereby exchanging critical messages aimed at enhancing road safety, reducing traffic congestion, and enabling new services and applications for drivers and passengers. Due to its unique characteristics, VANETs have succeeded in enhancing transportation efficiency and safety. However, VANETs are vulnerable to black hole attacks, where malicious nodes discard packets, compromising safety. Existing solutions suffer from high overhead or infrastructure dependence. We propose a lightweight enhancement to AODV using dual-confirmation (RepAck/Info packets) to detect and isolate attackers in real time. Simulations show a 98% improvement in packet delivery ratio under attack, with minimal protocol modifications. While routing overhead increases by 25%, this trade-off ensures reliable communication in dynamic VANETs.